Sudden hearing loss caused by labyrinthine hemorrhage - Raquel Salomone; Taleb Abdu Ali Abu; Adriana Gonzaga Chaves; Maria Carmela Cundari Bocalini; Andy de Oliveira Vicente; Paulo Emmanuel Riskalla (Brazilian Journal of Otorhinolaryngology, 2008)
Summary: Sudden sensorineural hearing loss is relatively frequent. In most cases, the etiology is not discovered. One of the possible causes for sudden deafness is inner labyrinth bleeding, which was difficult to diagnose before the advent of magnetic resonance imaging. The purpose of this paper is to report a case of sudden hearing loss caused by a labyrinthine hemorrhage, and to present a review of the literature on this topic. Keywords: vertigo, hearing loss, sudden deafness